Biography or Hagiography: The Story of Sengya 僧崖 in the Continuing Biographies of Eminent Monks - Limei Chi (Religions)
This paper examines how Daoxuan 道宣, the Tang Dynasty Buddhist historian and founder of the Nanshan Vinaya School, meticulously constructed the saintly image of Sengya 僧崖—a monk renowned for his auto-cremation—in his Continued Biographies of Eminent Monks (Xu gaoseng zhuan 續高僧傳). Drawing on a range of sources—including the now-lost Biography of the Bodhisattva Sengya and regional texts such as the Collection of Miscellaneous Records from the Shu Region—Daoxuan reconfigured Sengya’s narrative, presenting his auto-cremation as a profound religious sacrifice emblematic of transformative spiritual commitment. The analysis explores how Daoxuan navigated the doctrinal tensions between this extreme practice and the Vinaya precept of non-killing by emphasizing the practitioner’s mental state over the physical act. In doing so, he reframed self-immolation not as an aberration but as a legitimate, even exalted, path to liberation. This reinterpretation is situated within the broader context of Chinese Buddhist thought—particularly the ideas of the indestructibility of the spirit and the cosmological framework of “Heaven–Man Correspondence”—highlighting the interplay between religious symbolism, doctrinal adaptation, and lived practice. Crucially, this paper treats Daoxuan’s narrative not merely as biography, but as hagiography—a literary mode in which historical memory and religious narrative are inextricably entwined. By examining the rhetorical and ideological dimensions of this genre, this study contributes to a more nuanced understanding of how religious hagiography functioned as a tool for shaping sainthood, authorizing extreme religious practices, and negotiating the spiritual and social landscapes of medieval China.